Energy Consumption Evaluation of NoSQL DBMSs - Gomes, Carlos; Tavares, Eduardo; de O. Junior, Meuse Nogueira (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2016: Anais do XV Workshop em Desempenho de Sistemas Computacionais e de Comunicação, 2016)
Over the years, NoSQL Database Management Systems (DBMS) have been adopted as an alternative to the constraints of relational/SQL DBMSs. In order to demonstrate their feasibility, works have evaluated NoSQL DBMSs regarding some performance metrics, but energy consumption has not been assessed. Indeed, energy consumption is an issue that should not be neglected due to the rise of energy costs and environmental sustainability. This paper presents a peformance and energy consumption evaluation of NoSQL DBMSs, more specifically, Cassandra (column), MongoDB (document-oriented), Redis (key-value). Experiments are based on YCSB benchmark, and results demonstrate energy consumption can vary significantly among the assessed DBMSs for different commands (e.g., read) and workloads.